Chapter 4 Promoting medical change in Restoration Ireland The chemical revolution and the patronage of James Butler, duke of Ormond (1610-88) - Elmer, Peter (Social Histories of Medicine, 2019)
This chapter seeks to situate James Butler, duke of Ormond, at the centre of an important patronage network for medicine in Restoration Britain and Ireland. It explores the Irish dimension of the emergence of the Society of Chemical Physicians and situates it against the background provided by the momentous Cromwellian period in Ireland. Particular attention is paid to Pierre Belon, a Huguenot physician patronised by Ormond who was involved in efforts to promote a spa at Chapelizod near Dublin.